300 MW boiler design study for coal-fired supercritical CO2 Brayton cycle. (5th May 2018) - Bai, Wengang; Zhang, Yifan; Yang, Yu; Li, Hongzhi; Yao, Mingyu
Abstract: Supercritical CO2 (S-CO2 ) Brayton power cycle has been considered as a promising alternative choice of conventional steam cycle for coal-fired power plants. A conceptual design of the boiler is conducted for a 300 MW single reheated recompression S-CO2 Brayton cycle for coal-fired power plant with turbine inlet parameters of 32 MPa/600 °C/620 °C. The conventional economizer (ECO) is replaced with the split heater (SH) to reduce the inlet temperature of cooling wall of the furnace as well as to recover the flue gas heat The technology adaption of S-CO2 power cycle for coal-fired power plant has been evaluated in terms of specific design of the 300 MW coal fired boiler as well as the whole thermodynamic cycle layout. The boiler design and off-design thermal calculation results show that the S-CO2 boiler proposed in this paper can match well with the entire coal-fired S-CO2 Brayton cycle power generation system and has a good boiler variation performance.